The Important Role of the School Committees in Implementing School Based Management - Cimailing, Novia; Fitria, Happy; Missriani, Missriani (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to describe the important role of the school committee in implementing school-based management at SMP Negeri 33 Palembang. The research used a qualitative descriptive approach. The research subjects were the principal, teachers, students, committee members, and student guardians.Data collection techniques are observation, interviews, and documentation. The validity of the data used triangulation and member check. Data were analyzed through data condensation steps, data display, and conclusion drawing. The results showed that the role of the school committee at SMP Negeri 33 Palembang was quite good. Student management seen the committee participated in the student admission process until student graduation. Curriculum management the school committee as the advisory body, support, controlling body and mediator / liaison.Financial management is the role of the school committee as a supervisor and a balance board in budgeting. The personnel area committee acts as the advisory board and oversees the recruitment of education personnel. Management of facilities and infrastructure of the school committee as a policy maker. Then management of school relations with the community committee act as a facilitator and liaison between the school and the community.